(untitled) (Italian Review of Legal History, 2020)
The issue of the permanence of theoretically anachronistic colonial institutions, if related to the historical period and the ideology of the legal system of the Ecuadorian Republican era, was closely linked to the problem of land and the legal status of indigenous peasants and, more precisely, to the problem of latifundios and servitude of indigenous people. The new system of law was born into a society whose reality was plural: the ethnic pluralism of the inhabitants of the young Ecuadorian republic was also matched by a pluralism of ancient cultural, linguistic, and legal traditions. This article analyses the forms of exploitation of indigenous labour in the Ecuadorian countryside and their inclusion in the new system of law (1830 - 1906), taking into account their pre-colonial history, and the consequences on the legal status of indigenous peasants from the colony to the first decade of the 20th century. It emphasizes the influence of social, economic, and political dynamics on the legislation enacted in indigenous matters by the central authorities (Crown and State) and the influence of customs in the application of the law through the study of the Concertaje Institute. The original purpose of the concertaje contract (Real instrucción sobre el trabajo, 1601) was to emancipate the natives from servile labour and encourage their autonomy. The concertaje, however, being part of a system based on the disparity of the subjects for whom it was intended, was applied, and declined accordingly, becoming another form of servile labour of the indigenous people in the colonies. The specific legislation of the 19th century repeated the same scheme as the colonial one, enacting laws for the protection of indigenous people, which did not remedy the root of the problem of servile labour (concertaje), but merely regulated secondary aspects, with the aim of not making destabilizing changes to the pre-established political and social order. The concertaje was in fact regulated by the general rules of the Civil Code (1861) regarding the location of personal services, which left room for customs and traditions in the determination of specific working conditions. The “customs” of the place were, in fact, identified with the realities of the haciendas, in which the natives were included in a system designed with the aim of linking their labour for life to the lands where they lived and worked. This legislation – inserted in the framework of a constitutional order that divided the people born in the republic into “Ecuadorians” and “citizens” on the basis of census and created two categories of Ecuadorians that reflected, in fact, the categories of the colonial era: literate landowners and all others – facilitated the transition from the status of indigenous conciertos, at least in theory free contractors, to indigenous huasipungueros linked to the land. The exchange of access to land with personal services was a practice that had existed since colonial times and was combined with the status of minor/inferior in the paternalistic legislation first of the Crown and then of the Republic. The open clause referring to customs, finally, made possible and legal the coexistence of forms of semi-slavery within a system that proclaimed itself egalitarian and anti-slavery. The concertaje was addressed as a problem in its own right only at the end of the 19th century, but only to the point where it was useful to the ruling liberal elite of the Coast, who needed to make use of the manpower tied to the estates belonging to the conservative elite of the Sierra. For this reason, despite the progressive reforms of the first decade of the liberal government (1895 - 1906), the concertaje remained in force. The ruling elite wanted the natives untied from the land, but in order to be able to tie them to the new economies; the indigenous peasants, huasipungueros, tied to the land, were seen as the land belonging to the manomorta (properties with pre-existing terms/conditions which didn’t allow them to circulate freely).